Trade secret laws, labor mobility, and innovations - Massimo Motta; Thomas Rønde (Copenhagen Business School (CBS), Department of Economics, 2002)
We show that when the researcher's (observable but not contractible) contribution to innovation is crucial, a covenant not to compete (CNC) reduces e.ort and profits under both spot and relational contracts. Having no CNC allows the researcher to leave for a rival. This alleviates a commitment problem by forcing the firm to reward a successful researcher. However, if the firm's R&D investment mainly matters, including a CNC in the contract is optimal, as it ensures the firm's incentives to invest.
hdl:10398/7490
Keywords: J30; K20; L14; O31; O34; 330; Innovation; intellectual property rights; labor contracts; poaching; relational contracts; start-ups